Memperkuat Identitas Lokal dalam Globalisasi Melalui Pariwisata dan Pelestarian Budaya - Deliana, Dian; Purbosaputro, Erwin; Sunyoto, Sunyoto; Sujatmiko, Sujatmiko; Suyamto, Suyamto (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of writing this work is to investigate strategies and challenges in strengthening local identity through tourism development and cultural preservation in the context of globalization. This research method uses literature studies to collect and analyze sources related to strengthening local identity through tourism and cultural preservation in the context of globalization. Data was obtained from academic databases, online libraries and other trusted sources, then analyzed thematically to identify main themes in formulating insights and recommendations regarding the sustainability of culture and traditions in the era of globalization. The result of this work is the integration of cultural preservation in tourism to support local identity in the era of globalization through cultural and technological understanding strategies. Early cultural awareness and cross-sector cooperation are important to preserve cultural diversity for future generations. Effective collaboration and implementation of appropriate strategies enable communities to safeguard their cultural heritage. Strategies to strengthen local identity through tourism include a holistic approach to local culture, implementation of regional regulations, and use of information technology. The use of digital platforms and social media is expected to promote the uniqueness of local culture globally, while the integration of information technology supports authentic and relevant tourism experiences. The aim is for the tourism sector to become a driving force in preserving cultural heritage for future generations.